Transient phenomena in power system due to switching - Tan, Doreen Yan Han. (2010)
Transient occurs when there is a sudden change in voltage or current in a system and this usually happens in operation of switching devices. Transients are process to electronic equipment for testing their performance and are show to induce fast transient oscillation directly, in the form of a damped sine wave, rather than attempt to reproduce the original source. Transients cause stress to be induced on the electrical grid. Stress causes resistance and excessive heat buildup in electrical equipment. Although transient only happen for a short period of time, they can also be large in magnitude, large enough to cause catastrophic damage to electrical equipment. With the increasing dependence on electricity supplies, the need to achieve an acceptable level of reliability, quality and safety at an economic price becomes even more important to customers. Therefore, in order to remain in the competitive market, it is of importance to have sufficient knowledge on the transients’ phenomena in power systems before one can design an excellent and dependable protective system.